APPLICATION OF ACOUSTIC IMPEDANCE INVERSION TO PREDICT THE “Y” FIELD RESERVOIR DISTRIBUTION - Komara, Eki; M.E.P, Desak Putu; Miftakhul F, M Haris; Satriana, Satriana (Jurnal Geosaintek, 2024)
Identification of accurate reservoir distribution is necessary to identify prospective and productive zones. One way to identify the distribution of reservoirs in the "Y" field is the inversion method. The inversion method used in this study is acoustic impedance inversion which can be relied upon to characterize the reservoir. This research was conducted to know the best acoustic impedance inversion method and identify the distribution of reservoirs in Field "Y". On research, there are 5 well data and PSTM 3D seismic data. The analytical method used compares the results of cross-section seismic of 3 methods inversion seismic, namely Model-based, Band-Limited, and Sparse spike to get layer prospect hydrocarbons. The goal is to determine the best inversion by identifying the smallest error value. After comparing the results of cross-section seismic and pre-analytical inversion, it has been determined that the Model-Based method is the most effective. This method provides results that support the cross-section and have a small margin of error with a good correlation value. The smallest RMS error value in the method of the model-based inversion is 1944.97 (ft/ s) * (g/cc). The reservoir in Field "Y" is identified as sandstone with an impedance value ranging from 24139 to 26722 (ft/s) * (g/cc) and a porosity value of 20 to 23%. It is located at a depth of -935 to -950 m on the Top Bekasap and at a depth of -1067 to -1078 m on the Bottom Bekasap.